Nutritional Status of Irish Older People in Receipt of Meals-on-Wheels and the Nutritional Content of Meals Provided - O'DWYER, CIARA MARY; TIMONEN, VIRPI (Wiley-Blackwell, 2009)
BACKGROUND: Research has suggested that meals-on-wheels recipients can be at risk for poor nutritional status. Despite this, few countries have statutory minimum requirements for the nutrient content of meals-on-wheels. This study examined both the nutritional status of a sample of Irish recipients and the nutrient content of a sample of meals provided to determine whether Irish recipients would benefit from statutory minimum nutritional standards. METHODS: The study had two phases. First, a nutritional assessment was carried out to analyse the nutritional status of a sample of Irish meals-on-wheels recipients (Mini Nutritional Assessment and 24-h dietary recall with 63 self-selected respondents). Second, an assessment of the nutrient content of a sample of 46 meals from eight meals-on-wheels services was undertaken to characterise the nutritional content of the meals. RESULTS: Over one-third of recipients (38.5%) were malnourished or at-risk of malnutrition and over half (52.3%) were overweight or obese. The mean (SD) energy [kJ (kcal)] content of the meals assessed was 3008 (498) kJ [719 (119.1) kcal], contributing 35-40% of the recommended dietary allowance (RDA) for males aged 65 years and over and 42-45% of the RDA for females aged 65 years and over. In the meals assessed, the levels of vitamin C (25.3%), vitamin D (11.6%), folate (24.8%) and calcium (20.9%) were below one-third of the Irish RDA for these nutrients. CONCLUSIONS: Irish recipients may not be receiving adequate micronutrients from meals-on-wheels. Legislation that sets out minimum standards for the nutrient content of meals-on-wheels and greater variation in the portion sizes offered may benefit recipients.
PUBLISHED
Keywords: Social Studies